Research on the correlation between positive psychological capital influence and the social behavior of students-using the example of Guangzhou city, China - Yifei, Yao; Asipova, Nurbubu; Zeng, Yulin; Huang, Wenya; Rysbaevna, Dzhooshbekova Ainagul (Edelweiss Applied Science and Technology, 2025)
This study focused on public elementary school students in Guangdong Province, China. After obtaining consent from teachers and parents, questionnaires were distributed for the students to complete, and were subsequently collected either by mail or in person. A random sampling method was used, based on the principle of 'sampling half of the upper-grade classes in each school,' to obtain 500 valid questionnaires as the study sample. This study found that children with two or three siblings exhibited more independent behaviors compared to only children, indicating the significant impact of sibling interactions on social behavior. For only children, the lack of opportunities for sibling interaction makes the development of positive social behaviors more difficult. Therefore, parents should provide more opportunities for their children to interact with peers of similar ages, such as cousins or neighbors, to increase their chances of social interaction.This study also found that among the senior students at the school, middle-born children exhibited poorer resilience, significantly lower than that of first-borns, last-borns, and only children. This suggests that middle-born children require more care and support from their families when facing obstacles, setbacks, or various pressures.